Enhancing self-regulated learning through using written feedback in higher education. (2017) - Ion, Georgeta; Cano-García, Elena; Fernández-Ferrer, Maite
Highlights: The necessity of transferring the protagonism from the tutors to the students in search of a more dialogic feedback. The feedback that is provided has been focused on feedforward, making reference to the future learning of the student. Despite the fact that both tutors and students acknowledge the value of feedback for the self-assessment and self-regulation of student learning, dissonance in students' and tutors' perception exists. Abstract: Feedback is considered to be a key component in teacher activity for the reflective construction of knowledge. This paper aims to analyse the feedback provided by lecturers in order to enhance students' self-regulation of their learning. The methods used consisted in the analysis of the content of feedback and questionnaires administered to students and lecturers. The results show that most of the feedback provided by lecturers is close to that of feedforward. Students evaluate this feedback in a very positive way, as they consider it to be useful when working through the content. It also makes them more aware of the competencies that they should reach.